Impact of polychaetes (Nereis spp. and Arenicola marina) on carbon biogeochemistry in coastal marine sediments† - Kristensen, Erik (BioMed Central, 2001)
Known effects of bioturbation by common polychaetes (Nereis spp. and Arenicola marina) in Northern European coastal waters on sediment carbon diagenesis is summarized and assessed. The physical impact of irrigation and reworking activity of the involved polychaete species is evaluated and related to their basic biology. Based on past and present experimental work, it is concluded that effects of bioturbation on carbon diagenesis from manipulated laboratory experiments cannot be directly extrapolated to in situ conditions. The 45–260% flux (e.g., CO(2 )release) enhancement found in the laboratory is much higher than usually observed in the field (10–25%). Thus, the faunal induced enhancement of microbial carbon oxidation in natural sediments instead causes a reduction of the organic matter inventory rather than an increased release of CO(2 )across the sediment/water interface. The relative decrease in organic inventory (G(b)/G(u)) is inversely related to the relative increase in microbial capacity for organic matter decay (k(b)/k(u)). The equilibrium is controlled by the balance between organic input (deposition of organic matter at the sediment surface) and the intensity of bioturbation. Introduction of oxygen to subsurface sediment and removal of metabolites are considered the two most important underlying mechanisms for the stimulation of carbon oxidation by burrowing fauna. Introduction of oxygen to deep sediment layers of low microbial activity, either by downward irrigation transport of overlying oxic water or by upward reworking transport of sediment to the oxic water column will increase carbon oxidation of anaerobically refractory organic matter. It appears that the irrigation effect is larger than and to a higher degree dependent on animal density than the reworking effect. Enhancement of anaerobic carbon oxidation by removal of metabolites (reduced diffusion scale) may cause a significant increase in total sediment metabolism. This is caused by three possible mechanisms: (i) combined mineralization and biological uptake; (ii) combined mineralization and abiogenic precipitation; and (iii) alleviation of metabolite inhibition. Finally, some suggestions for future work on bioturbation effects are presented, including: (i) experimental verification of metabolite inhibition in bioturbated sediments; (ii) mapping and quantification of the role of metals as electron acceptors in bioturbated sediments; and (iii) identification of microbial community composition by the use of new molecular biological techniques. These three topics are not intended to cover all unresolved aspects of bioturbation, but should rather be considered a list of obvious gaps in our knowledge and present new and appealing approaches.